2019
DOI: 10.1096/fasebj.2019.33.1_supplement.705.2
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Stem Cell‐Derived Exosomes Inhibit Doxorubicin‐Induced Pyroptosis in Cardiac Cells

Abstract: Doxorubicin (Dox) is a potent antineoplastic drug used to treat various cancers. Unfortunately, Dox administration is limited due to induction of adverse cardiotoxicity (DIC), which is mediated through oxidative stress, ER stress, and inflammation. However, it is unknown whether Dox induces an inflammasomne‐mediated cell death, called “pyroptosis” in heart. Pyroptosis occurs via activation of TLR‐4 receptor and generation of NLRP3 inflammasome in response to damage‐associated pattern molecules (DAPMs). This wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Exosomes contain RNA, lipids, and proteins and deliver signals to target cells, which is essential for intercellular communication and exchange of genetic information [ 17 ]. Exosomes derived from stem cells could inhibit inflammation and doxorubicin-induced pyroptosis in cardiac cells [ 11 , 18 , 19 ]. Dargani et al [ 18 ] indicated that doxorubicin promotes the expression of IL-1 β and IL-18 in exosomes derived from embryonic stem cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes contain RNA, lipids, and proteins and deliver signals to target cells, which is essential for intercellular communication and exchange of genetic information [ 17 ]. Exosomes derived from stem cells could inhibit inflammation and doxorubicin-induced pyroptosis in cardiac cells [ 11 , 18 , 19 ]. Dargani et al [ 18 ] indicated that doxorubicin promotes the expression of IL-1 β and IL-18 in exosomes derived from embryonic stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes derived from stem cells could inhibit inflammation and doxorubicin-induced pyroptosis in cardiac cells [11,18,19]. Dargani et al [18] indicated that doxorubicin promotes the expression of IL-1β and IL-18 in exosomes derived from embryonic stem cells. Evidence showed that the abundance of exosomal proteins, mRNA, and miRNA and exosomal therapeutic potential could be enhanced by hypoxia [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%